2015
DOI: 10.1002/hipo.22496
|View full text |Cite
|
Sign up to set email alerts
|

Place field repetition and spatial learning in a multicompartment environment

Abstract: Recent studies have shown that place cells in the hippocampus possess firing fields that repeat in physically similar, parallel environments. These results imply that it should be difficult for animals to distinguish parallel environments at a behavioral level. To test this, we trained rats on a novel odor‐location task in an environment with four parallel compartments which had previously been shown to yield place field repetition. A second group of animals was trained on the same task, but with the compartme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
152
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(165 citation statements)
references
References 34 publications
10
152
3
Order By: Relevance
“…1a ). Previous results have demonstrated that point of entry can modulate hippocampal representations across different compartments 911 . In our paradigm, entry to the single compartment through either doorway is associated with a distinct recent history including the animal’s spatial location, direction of running within the hallway, and the turns made as the mouse enters the larger 2D compartment.…”
Section: Resultsmentioning
confidence: 99%
“…1a ). Previous results have demonstrated that point of entry can modulate hippocampal representations across different compartments 911 . In our paradigm, entry to the single compartment through either doorway is associated with a distinct recent history including the animal’s spatial location, direction of running within the hallway, and the turns made as the mouse enters the larger 2D compartment.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, across multiple interconnected spaces (i.e., within ES) often cells are not firing at a unique location only. Rather, the same cell may fire again (is reused) within different vista spaces (Grieves, Jenkins, Harland, Wood, & Dudchenko, 2016;Skaggs & McNaughton, 1998;Spiers, Hayman, Jovalekic, Marozzi, & Jeffery, 2015). Transferred to the present experimentation, a single place cell might fire in multiple corridors, but it will not do so at corresponding locations within a single VS room.…”
Section: Discussionmentioning
confidence: 97%
“…Recurrence in spatial firing patterns has also been reported in several other structures, most notably in the form of grid cells of the mEC or repeating place fields of the HPC [27][28][29][30][31][32][33][34][35][36][37][38][39][40] . However, the current findings differ from previous work in several important ways.…”
Section: Discussionmentioning
confidence: 68%